Study guides

☆☆

Q: Factor this 9x2 plus 27

Write your answer...

Submit

Still have questions?

Related questions

= 53 9x3 + 9x2 + 5x1+ 3x1 27 + 18 + 5 + 3

Factor: 9x2 - 25.

(-3x - 1)(3x - 7)

9x2 + 9x - 10 =(3x - 2)(3x + 5)

3x

(3x - y)(3x - y)

9x2 + 12x + 4 = 9x2 + 6x + 6x + 4 = 3x(3x + 2) + 2(3x + 2) = (3x + 2)(3x + 2) = (3x + 2)2

(3x + 4)(3x + 4)

3x and x^2 - 3x + 1

9x2+11x-14 = (9x-7)(x+2) when factored with the help of the quadratic equation formula.

(3x - y)(3x - 5y) and (2x + 1)(2x + 11)

9x2 - 18x + 99(x2 - 2x + 1)==========

People also asked